Overdischarge and Aging Analytics of Li-Ion Cells. Issue 9 (6th July 2020) - Juarez-Robles, Daniel; Vyas, Anjul Arun; Fear, Conner; Jeevarajan, Judith A.; Mukherjee, Partha P.
Abstract : Overdischarge is a potential problem in large battery packs since cells in a series string are discharged under the same load, despite having different capacities. Although a single overdischarge does not necessarily cause a safety hazard, it forces electrodes outside their safe potential range and adversely affects the integrity of cell components. This work aims to fill the knowledge gap about the combined effect of aging-induced and overdischarge–induced degradation mechanisms. Graphite/LCO pouch cells are cycled at a moderate rate using four lower cutoff voltages: 2.7 V, 1.5 V, 0.0 V, and −0.5 V. The cells aged above the onset of reverse potential have an extended cycle life with aging-induced solid electrolyte interphase (SEI) growth and electrolyte decomposition as the main degradation mechanisms. In contrast, the cells aged under reversal condition (Elower ≤ 0.0 V) exhibit fast degradation, dictated by the interplay among lithium plating, cathode particle cracking, and dissolution of Cu current collector. The analysis is complemented with a comparative study of various state of health (SoH) indicators, including an internal resistance based dimensionless SoH descriptor. The results prove that overdischarge-induced abuse although benign, may turn into a malignant condition when alternated with continuous charging.